The Influence of Innovative Learning Management on the Numeration Skills of Primary School Students in Medan City - Lisnasari, Srie Faizah; Jainab, Jainab; Datten, Datten; Pelista, Pelista (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study was motivated by the low numeracy skills of students in Medan City, which reached only 50% in 2020 and increased to 62% in 2024. One contributing factor is the lack of variety in teaching methods and unengaging learning media, highlighting the need for innovative approaches to enhance students' numeracy skills. This study aims to analyze the impact of innovative teaching methods, such as environment-based gamification, digital educational games, and place value board media, on elementary school students' numeracy abilities. Using a quantitative method with a quasi-experimental design, this research involved 105 first and fifth-grade students from several elementary schools in Medan City. The findings indicate that innovative methods significantly improved students’ numeracy skills. At UPT SD Negeri 064026 Medan Tuntungan, the application of place value board media increased the post-test scores of Class V-A from 44.17 to 78.5 and Class V-B from 42.97 to 87.4 (t-value 2.63 > t-table 1.68). At UPT SDN 060972 Simalingkar B, digital educational games raised the experimental class score from 32 to 89.09 (t-value 2.97 > t-table 2.021). Meanwhile, in Class I of UPT SD Negeri 064026, the environment-based gamification method increased Class 1A’s score from 57 to 78.5 and Class 1B’s score from 44 to 88.25 (t-value 2.09 > t-table 2.04). Thus, innovative teaching methods significantly impact the improvement of elementary students’ numeracy skills in Medan City.